BREVE PERCURSO SOBRE A POLÍTICA HABITACIONAL BRASILEIRA - Sibila Corral de Area Leao Honda (Universidade do Oeste Paulista, 2009)
The fast process of urbanization in Brazil in recent decades has generated great discussions on urban reform, public policy and urban management. With 1988 Federal Constitution, these topics are in the spotlight, articulated by the city council as an equal federal entity and common jurisdiction in matters of urban policy. In this area, the question of housing policy becomes central and strategic for the city, as one of the main problems is the provision of adequate housing to the majority of the population. The Statute of the Cities (Estatuto das Cidades) in 2001, confirms this view. According to the National Housing Plan (Plano Nacional de Habitação) (Ministério das Cidades, 2004), with the decentralization process, the management of social programs, among them the housing, either by themselves or by joining a federal program becomes responsibility of the state and city councils. It is in this context that new sources of financing are created sponsored by the federal government through Caixa Econômica Federal, benefiting both the state and local governments and also a share of the private sector. Therefore, this article will outline the path of housing policies in Brazil, through a survey of policies, plans and federal government programs, observing the neglect given to the planning of cities and the problems caused by unplanned urban expansion.